An alternative cinema of poverty: Understanding the Taiwanese-language film industry. Issue 2 (31st July 2020) - Berry, Chris
Abstract: The term taiyupian refers to over one thousand low-budget, Taiwanese-language films made between the mid-1950s and early 1970s. How should we understand this industry? It was neglected and forgotten for many years. By the time scholars became interested in the 1990s in revisiting taiyupian as part of the 'sadness' of the island's martial law era, only 178 complete films survived. More recently, they have been revalorized and promoted as cult movies. In response to the limitations of those frameworks, this essay proposes approaching taiyupian as an alternative 'cinema of poverty.' Here, cinema of poverty is not a derogatory remark. Nor is it praise for high modernist purism, along the lines proposed by Jerzy Grotowski in his concept of a theatre of poverty. Rather, it is an analytical term, referring to the adoption of ingenious methods to realize a Hollywood-style cinema industry and culture on a low budget. In other words, this alternative cinema of poverty was also a cinema of aspiration. The essay asks if this practice can be considered as an exuberantly commercial practice of what Lu Xun in the 1930s called 'grabbism' ( nalai zhuyi ), appropriating anything that works from other cultural forms and overseas to create a locally distinctive cosmopolitanism of the poor. Furthermore, it argues that the idea of the taiyupian industry as an alternative cinema of poverty places it in a lineage of similarly neglected popular and commercial film industries that emulated Hollywood on a budget here.